Evaluation and optimization of bio‐optical inversion algorithms for remote sensing of Lake Superior's optical properties. Issue 4 (3rd April 2013) - Mouw, Colleen B.; Chen, Haidi; McKinley, Galen A.; Effler, Steven; O'Donnell, David; Perkins, Mary Gail; Strait, Chris
Abstract : [1] Satellite remote sensing offers one of the best spatial and temporal observational approaches. However, well‐validated satellite imagery has remained elusive for Lake Superior. Lake Superior's optical properties are highly influenced by colored dissolved organic matter (CDOM), which has hindered the retrieval of chlorophyll concentration through band‐ratio algorithms. This study evaluated seven existing inversion algorithms. The top‐performing inversion algorithm was tuned to a Lake Superior optical data set and applied to satellite imagery. The retrieval of chlorophyll concentration via inversion algorithms was not possible due to errors in derived CDOM absorption being greater than phytoplankton absorption values and the very small contribution of phytoplankton absorption to the overall absorption budget. However, the retrieval of absorption due to CDOM from satellite imagery was encouraging. To ensure that the best satellite remotely sensed reflectance estimates were used in the retrieval of absorption due to CDOM, several atmospheric correction schemes were evaluated. The absorption due to CDOM was greatest in the western arm of Lake Superior and near river mouths and decreased with distance offshore. The absorption due to CDOM had a bimodal distribution over the annual cycle with the greatest peak in fall and a smaller peak in spring. Key Points: The QAA algorithm and the updated NASA atmospheric correction performed best Retrieval of chlorophyll concentration via inversion algorithms was not possible A CDOM retrieval performance was encouraging and displayed peaks in spring/fall